Development and Validation of Crosswalks Between FIM® and SCIM III for Voluntary Musculoskeletal Movement Functions. (October 2021) - Jones, Linda A. T.; Li, Chih-Ying; Weitzenkamp, David; Steeves, John; Charlifue, Susie; Whiteneck, Gale
Background . In spinal cord injury, there are multiple databases containing information on functional recovery, but data cannot be pooled or compared due to differences in how function is measured. A crosswalk is needed to link or convert scores between instruments. Objectives . To create a crosswalk between the voluntary musculoskeletal movement items in the Functional Independence Measure (FIM®) and the Spinal Cord Independence Measure III (SCIM III) for spinal cord injury. Methods . Retrospective datasets with FIM® and SCIM III on the same people were used to develop (Swiss dataset, n = 662) and validate (US, n = 119, and Canadian datasets, n = 133) the crosswalks. Three different crosswalk methods (expert panel, equipercentile, and Rasch analysis) were employed. We used the correlation between observed scores on FIM® and SCIM III to crosswalked scores as the primary criterion to assess the strength of the crosswalk. Secondary criteria such as score distributions, Cohen's effect size, point differences, and subgroup invariance were also evaluated. Results . All three methods resulted in strong correlation coefficients, exceeding the primary criterion value of r = .866 (.897–.972). Assessment of secondary criteria suggests the equipercentile and Rasch methods produced the strongest crosswalks. Conclusions . The Rasch FIM®/SCIM III crosswalk is recommended because it is based on co-calibration of linearized measures, allowing for more sophisticated parametric analyses. The crosswalk will allow comparisons of voluntary musculoskeletal functional recovery across international databases using different functional measures, as well as different systems of care and rehabilitation approaches.